2010
DOI: 10.1016/j.jeurceramsoc.2009.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Transparent polycrystalline alumina using spark plasma sintering: Effect of Mg, Y and La doping

Abstract: Transparent polycrystalline alumina (PCA) is a promising replacement for sapphire. Its optical properties however are highly dependent on the grain size and residual porosity which need to be controlled for real inline transmittances (RIT), that are high enough for possible applications.To achieve high RITs, doping as well as pressure assisted sintering is often used. In this study spark plasma sintering (SPS) and doping are investigated. A systematic experimental design is used to study the influence of Mg, Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
95
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 30 publications
4
95
0
1
Order By: Relevance
“…Experimental studies however indicate that below the solubility limit and at the same dopant concentration and sintering conditions, La and Y doped samples have approximately the same grain size. 43,46,47 The effect on creep resistance is also reported to be either very similar 45,46 or even less for La than for Y. 47 From the present results two possible indications as to why La is not more effective than Y can be gained.…”
Section: Lanthanum Segregationsupporting
confidence: 57%
See 2 more Smart Citations
“…Experimental studies however indicate that below the solubility limit and at the same dopant concentration and sintering conditions, La and Y doped samples have approximately the same grain size. 43,46,47 The effect on creep resistance is also reported to be either very similar 45,46 or even less for La than for Y. 47 From the present results two possible indications as to why La is not more effective than Y can be gained.…”
Section: Lanthanum Segregationsupporting
confidence: 57%
“…Both dopants are known to decrease grain growth during sintering 42,43 and increase the high-temperature creep resistance [44][45][46][47][48][49] of ␣-alumina. Grain boundary segregation rather than second phase precipitation is the cause of these effects, as they occur below the solubility limit.…”
Section: Lanthanum Segregationmentioning
confidence: 99%
See 1 more Smart Citation
“…For both mechanical and economical reasons, numerous studies have been performed over recent years to replace sapphire by transparent polycrystalline alumina (PCA) in various optical applications such as discharge lamp envelopes and optical windows or armour [1][2][3][4][5]. The light transmission properties of fine-grained PCA can be described by the Apetz and van Bruggen model [6], based on the Rayleigh-GansDebye approximation.…”
Section: Introductionmentioning
confidence: 99%
“…SPS is a processing technique that has been widely used over the past decades [1,5,[17][18][19][20]. It was shown that dense, finegrained materials can be developed at low temperatures and short sintering times compared to conventional techniques such as hot isostatic pressing (HIP).…”
Section: Introductionmentioning
confidence: 99%